Imaging findings and treatment in coccydynia – update of the recent study findings - Sukun, Abdullah; Cankurtaran, Tijen; Agildere, Muhteşem; Weber, Marc-André (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Background Coccydynia is one of the most overlooked symptoms in clinical practice. The diagnosis and radiologic findings of traumatic coccyx can be more easily detected unless it is delayed and postponed. For idiopathic coccydynia, which accounts for one third of cases, patients present with long-standing pain and multiple physician visits.Method The keywords coccyx, coccydynia, coccygodynia were searched in PubMed, Embase, Scopus databases in the last 5 years. Research articles, reviews and case reports were analyzed. The studies conducted in the last 5 years were presented under the headings of etiology, radiologic assessment, interventional and surgical treatments.Results and Conclusion The first step is dynamic X-ray of the coccyx in standing and sitting position. In this way, morphologic parameters and hypermobility causing idiopathic coccydynia can be evaluated. Morphologic and morphometric features of the coccyx described in previous CT and MR studies have explained the relationship with coccydynia. The key features are as follows: Type II coccyx morphology, subluxation of the intercoccygeal joint, presence of bony spicules. Knowledge of these definitions as well as the differential diagnosis in this anatomical region will help in reaching the correct diagnosis. The treatment of coccydynia is stepwise like the diagnosis. Conservative treatments are initiated first. Manipulations, ganglion impar block, injections, radiofrequency and shock treatments and finally coccygectomy are treatment methods reported. Radiologists should not overlook this region and should be familiar with the coccyx’s morphologic appearance and the sacrococcygeal region’s differential diagnosis.Key points Citation Format
Keywords: coccydynia; coccyx fractures; coccygeal hypermobility; imaging findings; treatment in coccydynia